Prevalence of Methicillin Resistant Staphylococcus aureus among Dumpsite Workers in Kathmandu Valley - Manandhar, Dinju; Subedi, Binita; Sharma, Dikshya; KC, Kelija; Shakya, Ashika; Shrestha, Angela (Tribhuvan University Journal of Microbiology, 2021)
Objectives: The main objective of this study was to determine prevalence of methicillin resistance Staphylococcus aureus among dumpsite workers. Methods: Total 60 nasal swab samples were collected. Conventional microbiological methods were used to isolate and identify S. aureus. Antibiotic susceptibility test was performed by Kriby Bauer disc diffusion method. MRSA was confirmed by using Cefoxitin disc. The organism showing resistance against three or more class were considered as MDRSA. Results: The prevalence rate of S. aureus and MRSA was found to be 46.67% (28/60) and 6.67% (4/60) in total population. The nasal carriage rate of S. aureus was found to be higher in age group 28-37 (70.06%, 12/17), gender male (47.5%, 19/40), district Kathmandu (70%, 14/20) and dumpsite workers (50%, 15/30). The isolated S. aureus were resistant to Penicillin (35.7%), Erythromycin (35.7%), Cefoxitin (14.3%) and Oxacillin (10.7%). S. aureus was susceptible (100%) to Tetracycline, Gentamycin, Ciprofloxacin, Co-trimoxazole, Chloramphenicol, and Vancomycin. Multidrug resistant S. aureus was not found in community of Kathmandu Valley. Conclusion: The study shows prevalence of MRSA strains of S. aureus in Kathmandu Valley. The occurrence of MRSA indicates development of Community acquired-antibiotic resistant bacteria.